Identifying key influencing factors of cross-regional railway infrastructure interconnection: a fuzzy integrated MCDM framework - Simai Yang; Pengcheng Xiang; Xiaping Zhao; Yiting Wang; Mingming Hu; Yan Qian (Humanities & Social Sciences Communications)
Abstract Cross-regional railway infrastructure (CRI) plays an important role in promoting coordinated regional development. But current understanding on how to strengthen cross-regional railway infrastructure interconnection (CRII) and its influence mechanism is still very limited. This study constructed a conceptual model of CRII system to reveal the logic of CRII operation, and systematically identified 16 influencing factors. Meanwhile, an F-MCDM (F-Multi-criteria Decision Making) model was created to capture the interactions among the influencing factors, identifying eight key influencing factors and four possible countermeasures. The results revealed that policy and institutional innovation, incentives and investment ecology, efficient implementation and coordination mechanisms, and supply chain and technology security capacity are four crucial challenges for CRII. Among them, the cooperation modes between the central government and local governments, as well as among local governments, were identified as the most critical factors. Accordingly, a four-pronged framework of “policy alignment, cooperative incentives, operational excellence, and supply assurance” was developed to better promote CRII. This study contributes to a deeper understanding of CRII, enriches the body of knowledge on cross-regional transportation infrastructure interconnection, and provides theoretical support and decision-making references for policymakers to implement CRII.